Analisis Tingkat Kesehatan Bank - Rahayu, Riski; Ruma, Zainal; Anwar, Anwar; Sahabuddin, Romansyah; Paramaswary, Annisa (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
This research aims to determine the health level of PT. Bank Muamalat Indonesia Tbk which uses the RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) method. The research object is PT. Bank Muamalat Indonesia Tbk. The type of research used is quantitative descriptive research. The type of sample used is the financial report of PT. Bank Muamalat Indonesia Tbk from 2018 to 2022, while the type of data used is secondary data. The results of this research show that the health level of PT. Bank Muamalat Indonesia Tbk., in the period 2018 to 2022 as a whole is in the Healthy predicate with the risk profile aspect being in a Very Healthy condition with a final composite score of 90%, then the good corporate governance aspect is in a Healthy Enough condition with the final composite value was 68%, in the earning aspect it was in an Unhealthy condition with a final composite value of 40%, and finally in the capital aspect it was in a Very Healthy condition with a final composite value of 100%. Thus, assessing the health level of PT. Bank Muamalat Indonesia Tbk., it can be said that PT. Bank Muamalat Indonesia Tbk., was classified in the "HEALTHY" category for the last 5 years with a final composite score of 71.33%.